Responses of some selected Malaysian rice genotypes to callus induction under in vitro salt stress - Htwe, New Nwe; Mahmood, Maziah; Ho, Chai Ling; Qamaruz Zaman, Faridah; Mohd Zain, Abdullah (Academic Journals, 2011)
Tissue culture technique can be used as a source for genetic variability by means of genetic modifications through the process of in vitro cultures. This technique has been widely used for breeding purposes, especially for stress tolerance selection, which severely limits rice production. Also, the establishment of a suitable plant regeneration system is a prerequisite for successful genetic transformation. The aim of this study is to identify the most suitable medium and to assess the genotype performance for in vitro salt stress responses in some selected Malaysian rice genotypes. Differences in culture conditions, growth rate, plant hormone responses and accumulation of proline content were monitored. All the selected genotypes showed that the callus-growth capacities were significantly affected by the genotypes and the culture media. Evidently, callus was best induced on the MS medium added with 10 µM dichlorophenoxyacetic acid (2,4-D) and 0.4 gm/l casein hydrolysate. In addition, the shoot regeneration capacity from the callus was the most effective in ½ MS added with 10 µM 6 benzylaminopurine (BAP). The two genotypes, that is, MR219 (line 4) and MR219 (line 9), consistently performed the best in both callus culture (93.51 and 92.22%) and plant regeneration capacity (27.03 and 26.34%), respectively. When the callus were transferred to different concentrations of NaCl (0 to 250 mM) supplemented medium in order to examine their responses to salinity, the two genotypes, that is, MR219 (line 4) and MR219 (line 9), showed a significant decline in the callus growth (18.83 and 23.5%) and regeneration capacity (7.33 and 7.68%), respectively. A similar trend was also observed for the proline content. All the genotypes significantly resulted in proline accumulation. MR211 showed the highest accumulation, whereas MR219 (line 4) revealed the lowest proline accumulation. These proline content analyses further suggest potential salinity tolerance in the rice genotypes.